2010
DOI: 10.1111/j.1365-2923.2010.03720.x
|View full text |Cite
|
Sign up to set email alerts
|

Privacy, professionalism and Facebook: a dilemma for young doctors

Abstract: Young doctors are active members of Facebook. A quarter of the doctors in our survey sample did not use the privacy options, rendering the information they revealed readily available to a wider public. This information, although it included some healthy behaviours, also revealed personal information that might cause distress to patients or alter the professional boundary between patient and practitioner, as well as information that could bring the profession into disrepute (e.g. belonging to groups like 'Perve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
160
1
8

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 208 publications
(204 citation statements)
references
References 30 publications
7
160
1
8
Order By: Relevance
“…13 MacDonald et al reported that 65% of recent medical school graduates in New Zealand reported using Facebook. 18 Most recently, Moubarak et al reported that 73% of residents and fellows utilize Facebook. 9 Findings from the present study suggest that a significantly higher proportion of U.S. medical students (94%) report using OSNs for personal use than is suggested by these prior studies, although the percentage of resident users of OSNs (79.4%) is comparable to the Moubarak data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 MacDonald et al reported that 65% of recent medical school graduates in New Zealand reported using Facebook. 18 Most recently, Moubarak et al reported that 73% of residents and fellows utilize Facebook. 9 Findings from the present study suggest that a significantly higher proportion of U.S. medical students (94%) report using OSNs for personal use than is suggested by these prior studies, although the percentage of resident users of OSNs (79.4%) is comparable to the Moubarak data.…”
Section: Discussionmentioning
confidence: 99%
“…OSNs may lead to new kinds of patient-doctor interactions, raising questions about appropriate professional boundaries. 6,18,20,22,28 Physicians and physicians-in-training descriptively hold a variety of views regarding the ethical acceptability of such interactions, and the normative stance by medical professionals toward these interactions remains to be codified. 17 The nature of professional boundaries in the digital age is worthy of further reflection and investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers from the University of Otago Medical School in New Zealand surveyed young medical graduates regarding their use of Facebook; they found that a quarter of the doctors in the sample did not use the privacy options, rendering the information they revealed readily available to the wider public. As a result, they could violate the professional boundary between them and their patients (for example, by posting photos of their admitted patients without obtaining their permission) [24]. While this study does not represent Facebook users as a whole, it does raise the important point that users might not be aware of or concerned about the privacy of their personal information on social media.…”
Section: Social Media Websites and Ethical Challengesmentioning
confidence: 97%
“…Additionally, self-awareness includes understanding that unintended viewers can disseminate content from posts, as opposed to being viewed on a friendly, casual manner. [1] The associated consequences of unintended sharing of content from social media sites can be detrimental, including job termination. [1] …”
Section: Introductionmentioning
confidence: 99%
“…[1] The associated consequences of unintended sharing of content from social media sites can be detrimental, including job termination. [1] …”
Section: Introductionmentioning
confidence: 99%